Prevalence and predictors of Biker’s hand syndrome among the professional bike riders in Bangladesh: A cross-sectional study - Sohel Ahmed; Mohammad Jahirul Islam; G. M. Jakaria; Md Enamul Haque; Jalal Uddin; Tazveen Fariha; Md Saifur Rahman; Md Zahidul Islam; Raju Ahmed; Selim Hossain; S. M. Mahfuz Anwar (PLoS ONE, 2025)
Background The use of motorbikes for the rapid growth of ride-sharing platforms in Bangladesh and the increasing economic reliance on this occupation are significant sources of non-traumatic injuries, particularly those affecting the wrist and hand. This study aimed to determine the prevalence and factors that contribute to the occurrence of biker’s hand syndrome among bike riders in Bangladesh. Methods A cross-sectional study was conducted among professional bike riders using the Cornell hand discomfort questionnaire. This study includes 630 male bike riders from the cities of Dhaka and Sylhet in Bangladesh, selected through two-stage cluster sampling using a face-to-face interviewer-administered questionnaire. A binary logistic regression analysis was used to identify the factor that predicts biker’s hand syndrome. Results The prevalence of pain, ache, or discomfort was reported as 58.3% in the right hand (RH) and 51.3% in the left hand (LH). Participants who ride bikes with an engine capacity of less than 150cc (aOR 2.218, CI 1.192–4.128, p = 0.012 in RH and aOR 1.210, CI 0.672–2.157, p = 0.525 in LH), and uncomfortable handlebar (aOR 2.110, CI 1.171–3.801, p = 0.013 in RH and aOR 1.519, CI 0.888–2.598, p = 0.127 in LH) reported higher likelihood of hand syndrome. Individuals whose motorcycle does not fit their body physique have over five times higher odds of hand discomfort (aOR 5.136, CI 2.939–8.974, p < 0.001 in RH and aOR 3.676, CI 2.210–6.113, p < 0.001 in LH). Conclusion This study highlights a considerably greater occurrence of hand syndrome among professional bikers in Bangladesh. Implementing regular stretching exercises, the use of a comfortable hand gripper, and improving motorcycle-to-body fit could reduce hand syndrome risk by over fivefold. Policymakers and organizations involved in occupational health and safety should priorities taking appropriate measures to address this issue.